Remapping Athens: an analysis of urban cosmopolitan milieus - Tsilimpounidi, Myrto (2012)
The study makes a claim for a critical cosmopolitanism situated in daily performances and encounters of difference in Athens. In the wake of mass migration and economic crisis, the contemporary urban environment changes, creating new social spaces where identities and cultures interact. Festivals are seen as sites of creative dialogue between the Self, the Other and local communities. Festivals are examples of those new spaces where different performances of belonging give rise to alternative social imaginations. This study explores the emotional, cultural and political aspects of cosmopolitanism with the latter leading to the formation of an active civil society. As such, it seeks to evidence cosmopolitanism as an embodied, everyday practice. The research thus extends the current field by locating its empirical lens in a specific milieu. Empirical analysis of grounded cosmopolitanism anchored in behavioural repertoires redefines ubiquitous polarities of margin and centre, pointing towards social change in Athens. Fieldwork was conducted in Athens over eighteen months, comprising of building communities of participants involved in three festivals, including both artists and organisations. Research methods included observation and participation in the festivals, which were photographically documented for research visual diaries. Semi-structured interviews formed the core of the fieldwork. The approach allowed access to experiences, feelings and expressions through artworks, embodying ‘third spaces’. In the milieu of rapid social change, as urban localities transform as a result of economic and social crisis, the need for redefining politics emerges. The case studies explore how change in a celebratory moment can have a more sustainable legacy encouraging active citizenship. The analysis highlights the value of a model of cosmopolitanism in action, positing that transformation of the social and political must be local and grounded in everyday actions if it is to engage with promises of alternative futures